2010
DOI: 10.1007/s10295-010-0830-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory action of toxic compounds present in lignocellulosic hydrolysates on xylose to xylitol bioconversion by Candida guilliermondii

Abstract: The inhibitory action of acetic acid, ferulic acid, and syringaldehyde on metabolism of Candida guilliermondii yeast during xylose to xylitol bioconversion was evaluated. Assays were performed in buffered and nonbuffered semidefined medium containing xylose as main sugar (80.0 g/l), supplemented or not with acetic acid (0.8-2.6 g/l), ferulic acid (0.2-0.6 g/l), and/or syringaldehyde (0.3-0.8 g/l), according to a 2(3) full factorial design. Since only individual effects of the variables were observed, assays we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 22 publications
3
28
0
4
Order By: Relevance
“…3), and it inhibits cellulose hydrolysis in wet cake by endo-and exo-cellulases, and cellobiose hydrolysis by beta-glucosidase (77). The inhibitory effect of on metabolism of Candida guilliermondii yeast during xylose to xylitol bioconversion was evaluated and concluded that syringaldehyde may affect cell growth and metabolism of this organism (78). Furthermore, the inhibitory effects of syringaldehyde on a fermentation by Saccharomyces cerevisiae K35 was investigated and it was found that concentrations higher than 5 g/L of syringaldehyde were toxic (79).…”
Section: Phenolic Aldehydes Resulting From Lignin Hydrolysismentioning
confidence: 99%
“…3), and it inhibits cellulose hydrolysis in wet cake by endo-and exo-cellulases, and cellobiose hydrolysis by beta-glucosidase (77). The inhibitory effect of on metabolism of Candida guilliermondii yeast during xylose to xylitol bioconversion was evaluated and concluded that syringaldehyde may affect cell growth and metabolism of this organism (78). Furthermore, the inhibitory effects of syringaldehyde on a fermentation by Saccharomyces cerevisiae K35 was investigated and it was found that concentrations higher than 5 g/L of syringaldehyde were toxic (79).…”
Section: Phenolic Aldehydes Resulting From Lignin Hydrolysismentioning
confidence: 99%
“…Furfural, the dehydration product of pentoses, was commonly found in hemicellulose hydrolysis [6]. Pereira et al [7] reported that the inhibitors of acetic acid, ferulic acid, and syringaldehyde in fermentation substrate would affect microbial cell growth, xylose consumption, and xylitol yield during microbial fermentation for xylitol production. The toxicity of acetic acid was more severe under low pH conditions than under high pH conditions [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…If the employed yeast strain exhibits rather good tolerance to toxic substances, the complete removal of toxic compounds from the fermentation medium is not necessary (37) ; in fact, some toxic substances at low concentrations may even be beneficial to xylitol production. These yeasts exhibit good activity in degrading toxic substances and many small molecule impurities (acetic acid, furfural, phenol), which significantly improves xylitol fermentative production performance and effectively reduces the burden of physical and chemical purification or detoxification processes.…”
Section: Hydrolysis Of Biomassmentioning
confidence: 99%